2016
DOI: 10.1038/srep32146
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation behavior of AlxCoCrFeNi high entropy alloys under ion irradiation

Abstract: Materials performance is central to the satisfactory operation of current and future nuclear energy systems due to the severe irradiation environment in reactors. Searching for structural materials with excellent irradiation tolerance is crucial for developing the next generation nuclear reactors. Here, we report the irradiation responses of a novel multi-component alloy system, high entropy alloy (HEA) AlxCoCrFeNi (x = 0.1, 0.75 and 1.5), focusing on their precipitation behavior. It is found that the single p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Other studies show results in the same direction, with HEAs improving radiation tolerance in both fcc and BCC structures. 18,[26][27][28][29][30] Very recently, W-based quinary HEAs with diverse composition have been synthesized as potential materials for fusion applications. The authors observed the formation of Ti carbides and laves phases at large W concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show results in the same direction, with HEAs improving radiation tolerance in both fcc and BCC structures. 18,[26][27][28][29][30] Very recently, W-based quinary HEAs with diverse composition have been synthesized as potential materials for fusion applications. The authors observed the formation of Ti carbides and laves phases at large W concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Since first proposed in 2004, high entropy alloys (HEAs) or multicomponent complex alloys, which comprise at least five different elements in an equal or near-equal atomic fraction, have been attracting a great deal of research interest (Cantor et al, 2004;Yeh et al, 2004;Ye et al, 2016b;Miracle and Senkov, 2017). Many attractive mechanical and physical properties were reported from various HEAs, such as the combined high strength and ductility from CoCrFeMnNi (Li et al, 2016), the exceptional damage tolerance from CoCrNi and CoCrFeMnNi at cryogenic temperatures (Gludovatz et al, 2014(Gludovatz et al, , 2016Zhang et al, 2015b), high ion irradiation resistance (Zhang et al, 2015a;Yang et al, 2016), and the superb specific hardness from Al 20 Li 20 Mg 10 Sc 20 Ti 30 (Youssef et al, 2015). At the fundamental level, these promising properties could be attributed to the unique local atomic structure of HEAs.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Cr is distributed more uniformly in both brighter, coarser columnar grains and in darker areas. The brighter, coarser columnar grains and the bright fine dendrites in the darker areas exhibit the FCC crystal structure according to the references [12,29], determined by transmission electron microscopy. The dark fine dendrites exhibit the BCC crystal structure [12,17].…”
Section: Methodsmentioning
confidence: 78%
“…the FCC crystal structure according to the references [12,29], determined by transmission electron microscopy. The dark fine dendrites exhibit the BCC crystal structure [12,17].…”
Section: Phase Compositions and Microstructuresmentioning
confidence: 99%